2013
DOI: 10.1155/2013/361637
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Mesenchymal Stromal Cell Osteogenic Differentiation through Modified Surfaces

Abstract: Stem cells continue to receive widespread attention due to their potential to revolutionise treatments in the fields of both tissue engineering and regenerative medicine. Adult stem cells, specifically mesenchymal stromal cells (MSCs), play a vital role in the natural events surrounding bone healing and osseointegration through being stimulated to differentiate along their osteogenic lineage and in doing so, they form new cortical and trabecular bone tissue. Understanding how to control, manipulate, and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 64 publications
(97 reference statements)
0
23
0
Order By: Relevance
“…4 that generates enhanced implant stability and/or indeed accelerated healing following implantation [16].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…4 that generates enhanced implant stability and/or indeed accelerated healing following implantation [16].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The surface properties of the implant play an integral role for implant osseointegration (Le et al, 2007, Colombo et al, 2012). Also, the topography and chemistry of the surface properties can control the quantity and quality of adhered cells to the implant (Rosales-Leal et al, 2010, Logan and Brett, 2013). It has been reported that optimal surface roughness can lead to effective osseointegration (Halldin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, they are used in a wide range of medical applications such as catheters, artificial heart valve replacements, and orthopaedic and dental implants 3 . In recent years, many surface modifications have been incorporated into the design of biomaterials in the hope of improving their biological activity and host tissue integration 3,4 .…”
Section: Introductionmentioning
confidence: 99%